RECRUITMENT PATTERN TO THE UK EPILEPSY AND PREGNANCY REGISTER. Issue 11 (9th October 2013) - Campbell, Ellen; Russell, Aline; Smithson, WH; Parsons, Linda; Irwin, Beth; Morrison, Patrick; Hunt, Stephen; Craig, John; Morrow, Jim
Abstract : Aim: To assess the pattern of recruitment to the UK Epilepsy and Pregnancy Register (UKEPR). Methods: All registered pregnancies in the UKEPR were divided by postcode area. Number of referrals per 100, 000 population were calculated for each postcode area using 2001 census data. Results: Map as shown. Conclusions: Our analysis shows high numbers of referrals from Northern Ireland and Scotland, but very low numbers from many areas of England and Wales. This includes several areas known to host specialist epilepsy centres. Greater ease of referral to UKEPR may help to increase recruitment in England and Wales.